A Chronological Review of the Expansion of the Museum’s Role in Relation to Spatial Changes - Jun-Young Heo; Jae Hong Lee (Buildings)
This study aims to investigate a chronological review of the term museum, defined by the International Council of Museums (“ICOM”) and Korean laws, and explore how the museum definitions have been revised historically. Then, it argues how the museum architecture has been spatially changed and explores whether the revised social roles and ethical responsibilities would impact the restructuring of the spatial changes. To this end, it scrutinized new ideas, significant issues, orders of words, and implicit intentions of the museum definitions over time. It analyzed the data of spatial change projects, which were collected through web crawling of the Korean National e-Procurement System. Then, the spatial changes were categorized regarding functions and characteristics. Through an in-depth investigation of a literature review and case studies, the findings suggest that museums had been understood as a place for collecting, exhibiting, and enjoying materials. However, they have been required to play diverse roles, such as collecting, conserving, exhibiting, researching, and communicating heritage for education, reflection, and sharing knowledge over time. However, the issue of cultural enjoyment has come into focus in Korean laws after 2007, and, as a result, spatial changes (e.g., creating immersive experience center, renovating exhibition spaces, and improving convenience spaces) have taken place exclusively in national museums. Thus, it is clear that national museums are aware of the need to actively think about their role with regard to the public and how architecture corresponds to this.